Toxicological Profile and Anti-Inflammatory Effect of Mucoadhesive Gel from Residues of Agave sisalana and Punica granatum - Fracasso, Júlia Amanda Rodrigues [UNESP]; Sikina, Ingrid Yuri Galindo [UNESP]; da Costa, Luísa Taynara Silvério [UNESP]; Guarnier, Lucas Pires; Ribeiro-Paes, João Tadeu; de Ferreira, Fernando Yutaka [UNESP]; de Almeida, Luan Victor Coelho [UNESP]; de Castro Silva, Beatriz [UNESP]; de Barros Barbosa, Débora [UNESP]; Ximenes, Valdecir Farias [UNESP]; Venkli, Desirre [UNESP]; Viel, Amanda Martins; et al. (MDPI, 2023)
Inflammation is a natural protective reaction of the body against endogenous and exogenous damage, such as tissue injuries, trauma, and infections. Thus, when the response is adequate, inflammation becomes a defense mechanism to repair damaged tissue, whereas when the response is inadequate and persistent, the increase in inflammatory cells, cytosines, and chymosins impair tissue regeneration and promote a response harmful to the organism. One example is chronic tissue inflammation, in which a simple lesion can progress to ulcers and even necrosis. In this situation, the anti-inflammatory medications available in therapy are not always effective. For this reason, the search for new treatments, developed from medicinal plants, has increased. In this direction, the plants Agave sisalana (sisal) and Punica granatum (pomegranate) are rich in saponins, which are secondary metabolites known for their therapeutic properties, including anti-inflammatory effects. Although Brazil is the world’s leading sisal producer, approximately 95% of the leaves are discarded after fiber extraction. Similarly, pomegranate peel waste is abundant in Brazil. To address the need for safe and effective anti-inflammatory treatments, this study aimed to create a topical mucoadhesive gel containing a combination of sisal (RS) and pomegranate residue (PR) extracts. In vitro experiments examined isolated and combined extracts, as well as the resulting formulation, focusing on (1) a phytochemical analysis (total saponin content); (2) cytotoxicity (MTT assay); and (3) a pharmacological assessment of anti-inflammatory activity (phagocytosis, macrophage spreading, and membrane stability). The results revealed saponin concentrations in grams per 100 g of dry extract as follows: SR—29.91 ± 0.33, PR—15.83 ± 0.93, association (A)—22.99 ± 0.01, base gel (G1)—0.00 ± 0.00, and association gel (G2)—0.52 ± 0.05. In MTT tests for isolated extracts, cytotoxicity values (µg/mL) were 3757.00 for SR and 2064.91 for PR. Conversely, A and G2 exhibited no cytotoxicity, with increased cell viability over time. All three anti-inflammatory tests confirmed the presence of this activity in SR, PR, and A. Notably, G2 demonstrated an anti-inflammatory effect comparable to dexamethasone. In conclusion, the gel containing SR and PR (i.e., A) holds promise as a novel herbal anti-inflammatory treatment. Its development could yield economic, social, and environmental benefits by utilizing discarded materials in Brazil.
Keywords: herbal; inflammation; saponins